COSTA RICA: ANTI-RELIGIOUS HATE SPEECH IN THE 2018 NATIONAL ELECTIONS - Blanco Lizano, Randall (2023)
The article analyzes the production of anti-religious hate speech in the 2018 Costa Rican national elections. To do this, it discusses the debates on hate speech and discursive framing from the perspective of Bourdieu’s symbolic efficacy. Analytical corpus were worked from digital publications and the markers of hate speech proposed by Alonso Zarza were identified. Finally, it identifies and discusses the contents of said discourse and its consequences for culture and democracy.